Etiology, prevention, and early intervention of overuse injuries in runners: a biomechanical perspective - Hreljac, A. (Physical Medicine & Rehabilitation Clinics of North America, 2005)
Overuse running injuries occur frequently, and generally could be said to occur as a result of a runner maintaining a stress/frequency combination which puts a vulnerable musculoskeletal structure within the injury portion of a stress-frequency relationship. Given a runner's specific anthropometric and biomechanical stride characteristics, the causes of all overuse running injuries could be classified as training errors, and thus, all overuse running injuries should be preventable. One of the goals of future research should be to focus on developing simple screening processes that may assist medical practitioners in identifying runners who are at a high risk for overuse injury.